2008
DOI: 10.1021/jp803458x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Strength on Wetting Behavior

Abstract: We examine the evolution of prewetting phase behavior with substrate strength for a model Lennard-Jones system, which consists of monatomic particles interacting with a single structureless surface. Grand canonical transition matrix Monte Carlo simulation is used to characterize surface phase behavior for several wall strengths. Our results indicate that both wetting and prewetting critical temperatures increase with decreasing wall strength, with the former increasing at a faster rate than the latter. The two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 52 publications
8
31
0
Order By: Relevance
“…To this end, we calculate D for a series of temperatures for different associating fluids and linearly extrapolate to zero to evaluate the wetting temperature (T w ); the results are shown in Figure 7(a) for a smooth surface. For a non-associating fluid, using the aforementioned scaling relationship for the temperature range T ¼ 0.65-0.725, we found T w ¼ 0.5836 (2), which is in good agreement with the value reported by Sellers and Errington [44]. However, recently, Grzelak and Errington [45] found that the locus of the prewetting line in the vicinity of the bulk saturation line is sensitive to the system size and hence can affect the estimation of the wetting temperature.…”
Section: Molecular Physics 1245supporting
confidence: 90%
See 2 more Smart Citations
“…To this end, we calculate D for a series of temperatures for different associating fluids and linearly extrapolate to zero to evaluate the wetting temperature (T w ); the results are shown in Figure 7(a) for a smooth surface. For a non-associating fluid, using the aforementioned scaling relationship for the temperature range T ¼ 0.65-0.725, we found T w ¼ 0.5836 (2), which is in good agreement with the value reported by Sellers and Errington [44]. However, recently, Grzelak and Errington [45] found that the locus of the prewetting line in the vicinity of the bulk saturation line is sensitive to the system size and hence can affect the estimation of the wetting temperature.…”
Section: Molecular Physics 1245supporting
confidence: 90%
“…Recently, Errington and co-workers studied various aspects of the prewetting transition for the same system using the GC-TMMC method [43][44][45]. We employed the same methodology to evaluate the prewetting transition for associating fluids, and our results are in agreement with those of Errington and co-workers for the non-associating system.…”
Section: Molecular Physics 1243supporting
confidence: 74%
See 1 more Smart Citation
“…5,19,20 The scaling approach adopted here allows us to readily compare the wetting properties of ionic liquids with those of the base Lennard-Jones fluid (α = 0), which have been thoroughly investigated in earlier works. 1,2,21 We note that the potential examined in this study differs from the one used by Leroy and Weiss 5 in another important aspect. In their study, a parameter λ was used to modulate the dispersion interactions without affecting the repulsive part.…”
Section: Model Systemmentioning
confidence: 67%
“…This is the characteristic of a prewetting transition, and since the form of the curve is similar for 360 K, we can say that the critical prewetting temperature is T pw ∼354 ± 6 K (average between the highest temperature of the previous isotherm and 360 K). It should be noted that usually T w and T pw are connected by a continuous prewetting line [30].…”
Section: Resultsmentioning
confidence: 99%